ADALIMUMAB USAGE CASE IN A PATIENT WITH JUVENILE OLIGOARTHRITIS AND UVEITIS - L. A. Balykova; N. V. Ivyanskaya; T. N. Arzamaskina; E. V. Makarkina; Ya. V. Lavskaya (Педиатрическая фармакология, 2013)
The article presents a case of a severe progressive course of a juvenile arthritis refractory to the standard antirheumatic therapy. Due to oligosymptomatic disease onset and low adherence of the patient to treatment, the disease was characterized by development of polyarticular joint syndrome with destructive changes (aseptic whirlbone necrosis) and formation of uveitis complicated by a cataract and patient’s incapacitation. Prescription of adalimumab allowed reducing activity of the inflammatory process, considerably improving function of the affected joints, terminating pain syndrome and stiffness and inducing remission of uveitis.